Improving water, sanitation and hygiene in health-care facilities, Liberia - Abrampah, Nana Mensah (Bull World Health Organ, 2017)
PROBLEM: The lack of proper water and sanitation infrastructures and poor hygiene practices in health-care facilities reduces facilities’ preparedness and response to disease outbreaks and decreases the communities’ trust in the health services provided. APPROACH: To improve water and sanitation infrastructures and hygiene practices, the Liberian health ministry held multistakeholder meetings to develop a national water, sanitation and hygiene and environmental health package. A national train-the-trainer course was held for county environmental health technicians, which included infection prevention and control focal persons; the focal persons acted as change agents. LOCAL SETTING: In Liberia, only 45% of 701 surveyed health-care facilities had an improved water source in 2015, and only 27% of these health-care facilities had proper disposal for infectious waste. RELEVANT CHANGES: Local ownership, through engagement of local health workers, was introduced to ensure development and refinement of the package. In-county collaborations between health-care facilities, along with multisectoral collaboration, informed national level direction, which led to increased focus on water and sanitation infrastructures and uptake of hygiene practices to improve the overall quality of service delivery. LESSONS LEARNT: National level leadership was important to identify a vision and create an enabling environment for changing the perception of water, sanitation and hygiene in health-care provision. The involvement of health workers was central to address basic infrastructure and hygiene practices in health-care facilities and they also worked as stimulators for sustainable change. Further, developing a long-term implementation plan for national level initiatives is important to ensure sustainability.